Domain-wide regulation of gene expression in the human genome - Gierman, Hinco J. (Cold Spring Harbor Laboratory Press, 2007)
Transcription factor complexes bind to regulatory sequences of genes, providing a system of individual expression regulation. Targets of distinct transcription factors usually map throughout the genome, without clustering. Nevertheless, highly and weakly expressed genes do cluster in separate chromosomal domains with an average size of 80–90 genes. We therefore asked whether, besides transcription factors, an additional level of gene expression regulation exists that acts on chromosomal domains. Here we show that identical green fluorescent protein (GFP) reporter constructs integrated at 90 different chromosomal positions obtain expression levels that correspond to the activity of the domains of integration. These domains are up to 80 genes long and can exert an eightfold effect on the expression levels of integrated genes. 3D-FISH shows that active domains of integration have a more open chromatin structure than integration domains with weak activity. These results reveal a novel domain-wide regulatory mechanism that, together with transcription factors, exerts a dual control over gene transcription.